Alternative autophagy, brefeldin A and viral trafficking pathways. Issue 9 (1st September 2016) - Grose, Charles; Klionsky, Daniel J.
ABSTRACT: Two topics that have attracted recent attention in the field of autophagy concern the source of the membrane that is used to form the autophagosome during macroautophagy and the role of noncanonical autophagic pathways. The 2 topics may converge when considering the intersection of autophagy with viral infection. We suggest that noncanonical autophagy, which is sensitive to treatment with brefeldin A, may converge with the infectious cycles of certain DNA and RNA viruses that utilize membrane from the ER and cis-Golgi.